The association between dental insurance coverage, socio-economic status and use of dental care in adolescents - Ali Golkari; Mehrdad Vossoughi; Mahsa Mohammadi; Arghavan Behbahanirad; Maryam Bakhtiar (Shiraz University of Medical Sciences, 2018)
Background: Several items affect the use of dental services. The objective of this study was to assess the association between socio-economic status (SES) and dental insurance coverage with the use of dental services amongst Iranian adolescents aged 13-15 years old. Methods: In this cross sectional study, we used a researcher-made questionnaire to assess the association between socio-economic status (SES) and dental insurance coverage with the use of dental services in 423 Iranian adolescents aged 13-15 years old. Statistical Package for Social Sciences (SPSS) was used to analyze the data, generate descriptive statistics, and perform multiple logistic regressions. Results: Use of dental services was statistically significant amongst the students with dental insurance and parents with higher income (P<0.001), which was independent of the other socio-economic factors (parent's age, education and marital status). Conclusion: The results showed that one of the important policies to reduce inequality in dental care is to improve dental insurance coverage.